PENGARUH REBUSAN DAUN SALAM TERHADAP PENURUNAN KADAR ASAM URAT DI DESA MALANGGATEN KECAMATAN KEBAKKRAMAT KABUPATEN KARANGANYAR - Ditya Yankusuma; Pradita Putri (KOSALA : Jurnal Ilmu Kesehatan, 2016)
Introduction of this research is the result Uric acid is produced by the body, sothat its presence can be normal in the blood and urine. While the survey resultsindicate that approximately 20 residents suffer from gout. Results of preliminaryinterviews with several residents of approximately 10 people, they do not knowthat bay leaves can lower uric acid levels in the blood.Purpose of the study was to determine the effect of bay leaf decoction todecrease levels of uric acid in the village Malanggaten.Subjects of the study were all patients with uric acid in the village of the DistrictMalanggaten Kebakkramat number of 12 people who met the inclusion criteriawere already writers set.Results showed that there was an effect decoction of leaves to decrease levelsof uric acid in the village Malanggaten obtained test results with Dependentpaired t test (t test) by SPSS for windows series 18 with Î± = 5% (0:05) obtained p0.000 that p < 0:05, which means Ho rejected so that it can be concluded thatthere is influence of decoction of leaves to decrease levels of uric acid in thevillage Malanggaten.Conclusion of research is the effect of bay leaf decoction to decrease levels ofuric acid in the village of the District Malanggaten Kebakkramat .Keywords: Bay Leaf, Uric Acid